Immune dysregulation in preeclampsia: integrative analysis of peripheral transcriptomes and placental single-cell land-scapes - Zheng, Shu; Xu, Peng; Shen, Huimin; Shu, Chang (Frontiers in Immunology, 2025)
Preeclampsia (PE) is a pregnancy-specific disorder marked by systemic immune imbalance and placental dysfunction, yet the link between peripheral molecular changes and tissue-level immune alterations remains incompletely understood. In this study, we integrated bulk transcriptomic analysis of peripheral blood from pregnant women at high risk for PE with single-cell RNA sequencing (scRNA-seq) of placental tissues to identify key immune-associated genes and explore their functional relevance. Transcriptome-wide differential expression, immune cell deconvolution, co-expression network analysis, and machine learning–based feature selection led to the identification of five candidate genes. Among them, TCL1A, CLEC2B, and LGALS9 exhibited robust expression in both datasets and were subjected to transcriptional and post-transcriptional regulatory network analysis. Single-cell profiling revealed that these genes were distinctly expressed in B cells, natural killer (NK) cells, monocytes, and Hofbauer cells, with functional enrichment in immune activation, cytokine signaling, and immune tolerance pathways. These findings illuminate the molecular mechanisms underlying immune dysregulation in PE and highlight TCL1A, CLEC2B, and LGALS9 as promising biomarkers for early detection and mechanistic investigation of the disease.